2022
DOI: 10.2478/fhort-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Perceived functions of allotment gardens and their importance during the COVID-19 pandemic in Poland

Abstract: This article describes the changes taking place in the functions of allotment gardens, their perceived value, reasons for purchasing allotments and subjective (self-reported) assessments of their importance during the pandemic. A questionnaire survey was conducted among 203 owners of allotment gardens located in three highly urbanised cities in the Silesian Voivodeship (Southern Poland). Semi-structured questionnaires and non-standardised questionnaires were used to collect the data. The results demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 48 publications
(48 reference statements)
3
12
0
Order By: Relevance
“…This result was similar to that of Gerdes et al (2022) , showing that respondents with 15 years of experience had lower anxiety levels. Young respondents in their twenties consider gardening an investment, while the elderly consider gardening a health improvement and recreational function from growing fruits and vegetables ( Janus et al, 2022 ). The group with 3–4 days of free time produced the highest benefits, which may also be associated with the effect of age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result was similar to that of Gerdes et al (2022) , showing that respondents with 15 years of experience had lower anxiety levels. Young respondents in their twenties consider gardening an investment, while the elderly consider gardening a health improvement and recreational function from growing fruits and vegetables ( Janus et al, 2022 ). The group with 3–4 days of free time produced the highest benefits, which may also be associated with the effect of age.…”
Section: Discussionmentioning
confidence: 99%
“…, [36] , [33] ) and obtained gardening benefits during the COVID-19 pandemic ( [13.] , [25] , [35] , [28] , [59] ). Owing to the strict home-based prevention policies in Taiwan, outdoor and natural activities have been restricted.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 76.4% of children and adolescents reported that spending time outside in nature helped them to deal with stress caused by physical distancing, which translated to mitigated declines in subjective well-being (M = −0.39, SD = 0.73) and self-reported mental health (M = −0.35, SD = 0.89), compared to the ones not reporting those benefits (M = −0.70, SD = 0.87; M = −0.54, SD = 0.90). Janus, Szewczyk-Taranek, and Smrokowska-Reichmann (2022) , Poland Allotment garden owners (203, largest age group 41–50 years (28.6%), 49%) NR Observational, cross-sectional, quantitative/qualitative, online survey Investigate value and reasons for purchasing allotment gardens during COVID-19 Gardens Questions about perceived value and reasons for gardening Perceived value Questions about perceived value and reasons for gardening Relaxation was the most frequently reported benefit of a home garden across age groups (33–70% agreement) except in the <20 year-olds and 61-70 year-olds. For <20 year-olds and 61-70 year-olds, growing fruit and vegetables was most frequently reported (38% and 35% agreement, respectively).…”
Section: A1 Detailed Search Strategy Implementedmentioning
confidence: 99%